(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and subclinical characteristics of elderly patients with intertrochanteric femoral fractures (IFFs) and evaluate the outcomes of cementless long-stem hemiarthroplasty in this patient group at Ha Dong General Hospital. Subjects and Methods: A descriptive study combining retrospective and prospective elements was conducted on 35 patients over 60 years old with traumatic IFFs who underwent cementless long-stem hemiarthroplasty at Ha Dong General Hospital. The study period was reported from June 2022 to June 2024. Results: The average age of the 35 patients was 84.07 ± 7.93 years, with the 80–89 age group accounting for the highest proportion (54.3%). The majority of patients were female, with a female-to-male ratio of 2:1. All patients presented with unstable fractures classified as AO type A2.2 (51.4%) or A2.3 (48.6%), and exhibited osteoporosis of grade II (60%) or grade III (40%) according to Singh’s index. Notably, 88.6% of patients had at least one comorbidity, with an average of 2.1 ± 1.0 comorbidities per patient. The most prevalent comorbidities were hypertension (62.9%), cardiovascular disease (34.3%), and diabetes mellitus (28.6%).Pain Relief: The mean Visual Analog Scale (VAS) pain score significantly decreased from 7.37±1.17 preoperatively to 3.6±1.06 postoperatively (p<0.05). Functional Recovery: Functional outcomes, assessed using the Harris Hip Score, demonstrated progressive improvement over time. After 6 months, 60% of patients achieved good (42.9%) or excellent (17.1%) results.Complications: The overall postoperative complication rate was 11.4%. Of these, the infection rate was 3.4%. Conclusion: Cementless long-stem hemiarthroplasty is an effective method for treating intertrochanteric femoral fractures (IFFs) in elderly patients, especially in cases with grade II–III osteoporosis and unstable AO type A2 fractures. This method yields promising recovery outcomes, demonstrating significant improvement in pain relief and functional recovery.